Analysis of Arts and Culture Development Model for Increase Visitors in Bangkalan Halal Tourism - Suryo Tri Saksono; Ulvia Ika Surya (Future Science, 2023)
Tourist attraction management has several problems that must be considered. The lack of information about halal tourism in Bangkalan for tourists outside the region causes tourists to only visit famous destinations. Tourism management has not paid attention to the development of art and culture typical of the region. In addition, the managers do not yet have a suitable model as a foundation for developing art and culture to increase visitors to Bangkalan halal tourism. This is the main problem in this study. The main objective of this study is to find the best formula related to the art and culture development model to increase visitors to Bangkalan halal tourism initiated by researchers by getting input from stakeholders, namely tourism managers, art / cultural actors, surrounding communities, and tourism visitors, and district governments throughout Madura. The model to be used is the Structural Equation Model. Data in this study were collected through observation (questionnaire), interviews, and documentation. Latent variables considered in this model include Accessibility, Attraction, Amenity, Ancillary, and Tourist Visits. This strategy is handed over to the management of Bangkalan halal tour-ism to be implemented to Increase Visitors.